Um palimpsesto feminino: a Albertine de Proust - Betysa Baêta Martins Starling (2018)
This dissertation is the result of a research on the novel In Search of Lost Time, written by Marcel Proust. The research was developed in the scope of the Literary Studies and aimed to study the character Albertine under the prism of the notion of memory as a reconstructing and modifying agent of the past from later experiences. The analysis is anchored in the concept of resignification of the past, like approached by Jorge Luis Borges in the essay Kafka and His Precursors, and by Freud. The analysis of some parallel scenes of the novel and the construction of the female characters sought to illuminate important aspects of the narrative, among them the way Albertine incorporate traces of other personages and reverberate them. The results of this research defend the idea of Albertine as a palimpsest in which it is possible to glimpse constituent fragments of other female characters and whose presence in the narrative helps to give new meanings to some experiences of the narrator.